A Systematic Literature Review: Success Factors and Gamification Impact on Donation-Based Crowdfunding Campaign - Abdullah, Amna; Kuşakci, Ali Osman (International Review of Management and Marketing, 2025)
Gamification is a fast-growing technique that increases user engagement and motivation in donation-based crowdfunding (DCF). The impact of gamification on donor participation has gained attention as a critical digital engagement strategy in social media-integrated DCF platforms. This study uses a systematic literature review to investigate the essential success factors and influence of engagement drivers, especially gamification, on DCF campaigns’ success. The PRISMA method has been used to identify various success factors at campaign, fundraiser, and platform levels by analysing 104 relevant papers extracted from the literature. In the initial phase, research patterns were identified from the literature and presented visually. In the second phase, a conceptual framework has been formulated to comprehensively summarize the role of success factors and drivers in enhancing donor engagement and optimizing crowdfunding outcomes. This research contributes by highlighting the importance of engagement strategies and the potential of gamification on DCF platforms. The study also addressed the broader context of these platforms’ digitalization, which offers new ways for gamification integration into digital engagement strategies.